Um quilombo contestado : análise sobre o processo de demarcação de terras quilombolas - Oliveira, Natane Franciella de (2017)
The research investigates the effectiveness of the remaining quilombo communities’ territorial rights, prescribed in the Federal Constitution of 1988 and in the Convention 169 of the International Labor Organization. The Process of the Linharinho Quilombola Community in the north of the state of Espírito Santo will be my field of study and it is understood as a social construction, which aims to change the situation of the Community, giving it a special property title. With the enactment of Decree 4883/03 and several Normative Instructions, the demarcation and titling procedures were operationalized, and the competence to these acts was attributed to the National Institute of Colonization and Agrarian Reform. The concept of the Process, an official object that generates expectations and recreates the conflicting relationships in a register that is subject to social control by the public administration and the judiciary, is put on stage. Under the argument of legal certainty, such initiatives were analyzed as faces of a bureaucratization and slowness in the processes involving quilombola rights. The methodology employed was ethnography, which consists in visits to INCRA, interview with legal agents that worked in the examined Process, and analysis of the physical Process (ethnography on documents) in which the necessary acts to the demarcation were materialized. The tense relations of power between the quilombolas and the agribusiness, the temporalities, the representations and the racism present in the Process, demonstrate that the reality of territorial rights of ethnic minorities is still pervaded by obstacles, questionings, and denial